Analisis Risiko dan Mitigasi Bencana Angin Puting Beliung Berbasis Sistem Informasi Geografis - Shofa’ Nur Amirah Khairiyah; Andrias Andrias; Tahir Tahir; La Ode Nursalam (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2025)
Kendari City often experiences tornado disasters that cause many losses. A tornado disaster risk analysis needs to be conducted to reduce the losses. This study aims to determine the distribution of the risk of tornado disaster in Kendari city as well as mitigation efforts that need to be done based on the level of disaster risk. This type of research is quantitative descriptive research with spatial analysis. The results showed that Kendari city has 5 levels of risk of puting twister disaster. Very low risk level with a total land area of 4176,77 ha (15,13%), low risk level of 3.514,86 ha (12,74%), moderate risk level of 14.218,44 ha (51,52%), high risk level of 5.230,71 ha (18,95%), and very high risk level of 457,38 ha (1,66%). The tornado disaster mitigation plan can be carried out based on the priority of disaster risk in Kendari city. Mitigation in very high to high risk areas is prioritized on prohibiting development, improving disaster management systems, and conservation measures. Mitigation in moderate risk areas is prioritized on the implementation of building standard rules that take into account wind loads and material safety. Mitigation in low to very low risk areas is prioritized on limiting development so as not to result in land conversion.